If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2n = 67 Solving 5 + -2n = 67 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2n = 67 + -5 Combine like terms: 5 + -5 = 0 0 + -2n = 67 + -5 -2n = 67 + -5 Combine like terms: 67 + -5 = 62 -2n = 62 Divide each side by '-2'. n = -31 Simplifying n = -31
| 64-x=42 | | y-(-6)=2 | | 13x+5x=10 | | 5=17(4x+28) | | 5y=15y+60 | | -13.1+18w=18.2w-10.86 | | 2ab-5ab= | | 1341-4.5x=x | | -11+y=27 | | 2x+12=2x-48 | | 19.9y-9.98=1.29-9.37+20y | | x^2-2ax-3a^2=0 | | -11+38=27 | | 7x+3+8x+6=144 | | -10+8a=6(a-4) | | [2+-3]=-4 | | 54=2x^2+12x | | 5-4x=2-3x | | -8(24)+15=x | | f+11=-9 | | 13=x*1.25 | | 2x+4x-3+10=10x-19 | | X+(-y)=-y+x | | 80=2l+2*14 | | 7=32(5x+8) | | -10.5p=-5-11p | | u=8a-56 | | 7 = 32(5x+8) | | 7e^4x+8=14 | | 6-2n=16 | | 9c-3d=c | | 4b-9b+3=-32 |